Battery positive electrode material as well as preparation method and application thereof

By introducing an inert layer into the battery positive electrode material, the problem of structural collapse and phase change during circulation of transition metal layered oxide positive electrode material is solved, which significantly improves the cycle stability and capacity retention rate, which is suitable for large-scale production.

CN119601612AActive Publication Date: 2025-03-11SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411506340.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

During the charging and discharging cycle of existing transition metal layered oxide positive electrode materials of sodium ion batteries and lithium ion batteries, the de-embedding of Na causes collapse and phase change of the layered structure, resulting in cycle capacity decay and poor cycle stability.

Method used

By introducing an inert layer into the positive electrode material of the battery, the inert layer is generated by an irreversible phase change of the transition metal layered oxide material under the activation voltage, forming a 1-10nm-thick lithosaline inert layer, which is coated on the bulk phase layer.

Benefits of technology

It significantly improves the cycle stability and cycle capacity retention rate of the battery cathode material, simplifies the production process, and reduces energy consumption, making it suitable for large-scale production and commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601612A_ABST
    Figure CN119601612A_ABST
Patent Text Reader

Abstract

The invention discloses a battery positive electrode material and a preparation method and application thereof, the battery positive electrode material comprises a bulk phase layer and an inert layer coating the bulk phase layer, the bulk phase layer comprises a transition metal layered oxide material, and the inert layer comprises a transition metal oxide generated by the transition metal layered oxide material through irreversible phase change; during preparation, the transition metal layered oxide material can be prepared into a positive electrode and then assembled into a battery, and then the battery is subjected to high-voltage activation, so that the battery positive electrode material with a specific coating structure can be generated; experiments show that the battery positive electrode material has high cycle stability, the preparation process is simple, the energy consumption is low, the battery positive electrode material can be directly fused into the formation process of the existing battery, and a feasible technical path is provided for large-scale production and commercial application of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical devices, in particular to positive electrode materials used in sodium ion batteries and lithium ion batteries, and specifically to a battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium ion batteries (SIBs) have attracted widespread attention due to their abundant resources, high cycle efficiency and significant energy conversion efficiency. These characteristics make sodium ion batteries a beneficial supplement to lithium ion batteries (LIBs) and are suitable for fields such as low-speed vehicles and grid-scale energy storage. The positive electrode material is one of the key factors determining battery performance and cycle stability. x MO2 (M=Ti, V, Cr, Mn, Fe, Co, Ni) has the advantages of good safety, simple structure and easy synthesis. However, during the charge and discharge cycle of transition metal layered oxide materials, the insertion and extraction of Na will cause the collision and contraction of the layered structure, which will then cause the collapse and phase change of the layered structure, resulting in the decay of the cycle capacity; at the same time, when the charge exceeds its cut-off voltage, the capacity will be severely limited. For example, when NaCrO2 is charged above 3.8V (Na 1-x When x>0.5 in CrO2), NaCrO2 undergoes irreversible phase change and Cr ion migration, resulting in poor cycle stability. In order to solve the problem of poor cycle stability, patent CN117038873A discloses a layered oxide electrode material coated with surface asphalt. Although the surface asphalt coating method improves the cycle stability of the material to a certain extent, the preparation method of the material is too complicated. Summary of the invention

[0003] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved battery positive electrode material and a method for preparing the same. The battery positive electrode material has high cycle stability and a simple preparation process and can be directly integrated into the existing battery formation process.

[0004] The present invention also provides a battery positive electrode sheet and a preparation method thereof, a battery and a preparation method thereof. When the improved battery positive electrode material and the preparation method thereof of the present invention are used, not only the method is simple and the cost is low, but also the battery cycle stability can be greatly improved. In particular, the preparation process of the positive electrode material of the present invention can be directly integrated into the existing battery formation process, providing a feasible technical path for the large-scale production and commercial application of ion batteries.

[0005] In order to achieve the above object, a technical solution adopted by the present invention is:

[0006] A battery positive electrode material comprises a bulk layer and an inert layer coated on the bulk layer, wherein the bulk layer comprises a transition metal layered oxide material, and the inert layer comprises a transition metal oxide generated by an irreversible phase change of the transition metal layered oxide material.

[0007] In some embodiments of the present invention, the transition metal layered oxide material that generates the transition metal oxide in the inert layer comes from the surface portion of the transition metal layered oxide material in the bulk layer.

[0008] In some embodiments of the present invention, the thickness of the inert layer is 1-10 nm, further 2-6 nm.

[0009] According to some specific aspects of the present invention, the inert layer is a rock salt phase inert layer.

[0010] In some embodiments of the present invention, the transition metal layered oxide material in the bulk layer and the transition metal layered oxide material in the inert layer are unmodified, or coated and / or doped modified materials, respectively.

[0011] In some embodiments of the present invention, the chemical composition of the transition metal layered oxide material is Na x MO2, M is selected from transition metals.

[0012] Furthermore, M is selected from a combination of one or more of Ti (titanium), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), and nickel (Ni).

[0013] In some embodiments of the present invention, in the inert layer, the ratio of Na to M is 0.2-0.4:1; in the bulk layer, the ratio of Na to M is 0.5-1:1.

[0014] According to some preferred aspects of the present invention, the irreversible phase change comprises subjecting the transition metal layered oxide material to an electrochemical transformation under a voltage.

[0015] Furthermore, the inert layer is constructed in situ by an electrochemical method.

[0016] Another technical solution provided by the present invention is a method for preparing the above-mentioned positive electrode material for a battery, the method comprising:

[0017] voltage-activating a battery comprising a positive electrode comprising a transition metal layered oxide material;

[0018] After the voltage is activated, the battery positive electrode material is generated;

[0019] The voltage activation comprises: charging the battery to an activation voltage and discharging the battery after standing still; the activation voltage is greater than the cutoff voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change.

[0020] In some embodiments of the present invention, the preparation process of the positive electrode includes: uniformly mixing the transition metal layered oxide material, the conductive agent, the binder, and the solvent, coating the mixture on a current collector, and drying the mixture to prepare the positive electrode.

[0021] Furthermore, the conductive agent includes but is not limited to acetylene black (SP) and the like.

[0022] Furthermore, the binder includes but is not limited to polyvinylidene fluoride (PVDF) and the like.

[0023] Furthermore, the solvent includes but is not limited to organic solvents such as N-methylpyrrolidone (NMP).

[0024] Furthermore, the mass ratio of the transition metal layered oxide material, the conductive agent and the binder is 85-95:1-10:1-10.

[0025] According to some specific aspects of the present invention, the current collector includes but is not limited to aluminum foil.

[0026] According to some specific aspects of the present invention, during the preparation of the positive electrode, the drying can be performed in a vacuum oven at 100-130°C.

[0027] According to some specific aspects of the present invention, during the preparation process of the positive electrode, the positive electrode can be made by punching the dried intermediate.

[0028] In some embodiments of the present invention, the positive electrode can be prepared according to the above method or commercially available.

[0029] In some embodiments of the present invention, during the preparation of the battery positive electrode material, the battery includes a button half-cell or a full cell, or a soft-pack cell. Further, the NP ratio of the soft-pack cell is 0.9 to 1.2.

[0030] In some embodiments of the present invention, during the preparation of the positive electrode material of the battery, the negative electrode of the battery includes but is not limited to common negative electrodes such as commercially available hard carbon.

[0031] According to some preferred aspects of the present invention, the voltage activation is performed 1 to 15 times. Further, the voltage activation is performed 1 to 8 times.

[0032] In some embodiments of the present invention, during the voltage activation process, the charging is performed at a constant current and constant voltage at 0.01-1C, and the discharging is a constant current discharge.

[0033] In some embodiments of the present invention, when the transition metal layered oxide material is O3-NaCrO2 material, the activation voltage is 3.65-3.77V; when the transition metal layered oxide material is O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 When O2 material is used, the activation voltage is 4.15-4.27V.

[0034] In some embodiments of the present invention, the battery positive electrode material is obtained by disassembling the battery after the voltage activation.

[0035] In some embodiments of the present invention, under the voltage activation, the transition metal layered oxide material undergoes a phase change starting from the surface, and an inert layer on the surface is generated in situ to generate the battery positive electrode material having a coating structure.

[0036] In some embodiments of the present invention, the battery positive electrode material is in the form of particles of 0.5 to 1 μm, with regular morphology and planar angular shapes.

[0037] In some embodiments of the present invention, the O3-NaCrO2 material can be commercially available or prepared by the following method:

[0038] High temperature solid phase synthesis: Na2CO3 and Cr2O3 are mixed in a stoichiometric ratio of x:1, where x is 1±0.02. The raw materials are finely ground and placed in a tube furnace for calcination under an inert atmosphere and then cooled.

[0039] Furthermore, the heating rate of the sintering is 1-10°C / min, the calcination temperature is 900-1000°C, the calcination atmosphere is an inert atmosphere such as an argon atmosphere, and the calcination time is 9-15 hours, and more preferably, the calcination time is 12-15 hours. Finally, the temperature is lowered to 400-600°C at a cooling rate of 1-10°C / min, and then naturally cooled to room temperature to obtain O3-NaCrO2 material.

[0040] Another technical solution provided by the present invention is: a battery positive electrode material, which is generated by causing a transition metal layered oxide material to undergo an electrochemical transformation under an activation voltage, wherein the activation voltage is greater than the cutoff voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change.

[0041] Another technical solution provided by the present invention is: a battery positive electrode sheet, wherein the battery positive electrode sheet comprises the battery positive electrode material described above.

[0042] Another technical solution provided by the present invention is a method for preparing a positive electrode sheet of a battery, the method comprising:

[0043] (1) assembling a positive electrode comprising a transition metal layered oxide material into a battery;

[0044] (2) voltage activation of the battery; wherein the voltage activation comprises: charging the battery to an activation voltage, and discharging the battery after standing; the activation voltage is greater than the cutoff voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change;

[0045] (3) Disassemble the battery processed in step (2) to obtain the battery positive electrode sheet.

[0046] Another technical solution provided by the present invention is a battery, comprising the battery positive electrode sheet described above or the battery positive electrode sheet manufactured by the method for preparing the battery positive electrode sheet described above.

[0047] Furthermore, the battery may be a lithium ion battery or a sodium ion battery.

[0048] Another technical solution provided by the present invention is a method for preparing a battery, the method comprising a battery formation process, the formation process comprising:

[0049] The battery is voltage activated, wherein the voltage activation comprises: charging the battery to an activation voltage, and discharging the battery after standing; the activation voltage is greater than the cut-off voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change;

[0050] The battery includes a positive electrode comprising a transition metal layered oxide material.

[0051] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0052] During a large number of experimental studies, the present invention has found that by utilizing the irreversible phase change of transition metal layered oxide materials, an inert layer-coated positive electrode material can be directly generated, thereby making the bulk layer and the inert layer of the positive electrode material directly combined and better matched, thereby not only achieving a significant improvement in the cycle stability, but also because the precursor material of the inert layer is the same as the bulk layer and can even be directly a part of the bulk layer, the inert layer-coated positive electrode material can be directly generated by in-situ construction, greatly simplifying the production process.

[0053] Furthermore, the inventors of the present invention have overcome the traditional technical prejudice that transition metal layered oxide materials cannot be charged above the cut-off voltage; the present invention creatively uses charging above the cut-off voltage for the first time to activate the surface layer phase change of the transition metal layered oxide material, and realizes the in situ electrochemical method to construct an inert layer. This method not only does not reduce the cycle performance of the material, but also enables its cycle capacity to be maintained efficiently. In particular, this method overcomes the defect of the existing preparation of the coating layer requiring high-temperature calcination, greatly reduces energy consumption, and is relatively simple to operate. It can be directly integrated into the existing battery formation process, providing a feasible technical path for the large-scale production and commercial application of sodium-ion batteries or lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0055] Figure 1 This is the first high voltage activation range of O3-NaCrO2;

[0056] Figure 2 The first cycle voltage-specific capacity curve of Example 1 and Comparative Example 1 at 2-3.6V at 0.5C;

[0057] Figure 3 It is a cycle test curve diagram of Example 1 and Comparative Example 1 at 0.5C;

[0058] Figure 4 It is a cycle test curve diagram of Example 2, Example 3 and Comparative Example 2 at 0.5C;

[0059] Figure 5 The following are the cycle test curves of Example 1, Example 4 and Example 5 at 0.5C;

[0060] Figure 6 This is a STEM image of NaCrO2 activated by high voltage in Example 6;

[0061] Figure 7 This is a STEM image of NaCrO2 in Comparative Example 3 without high voltage activation;

[0062] Figure 8 The first-cycle voltage-specific capacity curve under high voltage activation of Example 6 and the first-cycle voltage-specific capacity curve without high voltage activation of Comparative Example 3;

[0063] Fig. 9 It is a cycle test curve diagram of Example 6 and Comparative Example 3 at 0.5C;

[0064] Fig.10The first cycle voltage-specific capacity curve under high voltage activation of Example 7 and the first cycle voltage-specific capacity curve without high voltage activation of Comparative Example 4;

[0065] Fig.11 It is a cycle test curve diagram of Example 7 and Comparative Example 4 at 0.5C. DETAILED DESCRIPTION

[0066] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0067] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0068] In the following, the O3-NaCrO2 material can be prepared by the following method:

[0069] High temperature solid phase synthesis: Na2CO3 (purchased from Shanghai Titan Technology Co., Ltd., brand: 60035F) and Cr2O3 (purchased from Sinopharm Chemical Reagent Co., Ltd., brand 10006918 Shanghai trial batch number: 20220826) were mixed in a stoichiometric ratio of 1:1. The raw materials were finely ground and placed in a tubular furnace for calcination under argon atmosphere. The calcination heating rate was 5°C / min, the calcination temperature was 1000°C, and the calcination time was 12 hours. Finally, the temperature was cooled to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature to obtain O3-NaCrO2 material.

[0070] Example 1: Sodium chromite positive electrode, button half-cell, 3.75V in-situ construction

[0071] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0072] Specifically:

[0073] Preparation of positive electrode: 3.6 g of O3-NaCrO2 material, 0.2 g of acetylene black (SP), and 4 g of 5% polyvinylidene fluoride (PVDF) glue (the solvent is N-methylpyrrolidone (NMP), 0.2 g of PVDF) are mixed evenly, and then 0.2 g of organic solvent N-methylpyrrolidone (NMP) is added. After mixing evenly, the mixture is evenly coated on aluminum foil, and then placed in a vacuum oven at 120°C and baked for 12 hours, and then punched into a positive electrode;

[0074] Preparation of sodium ion button half-cell: Assemble the above-made positive electrode into a sodium ion button half-cell; put the spring, gasket, sodium sheet (negative electrode), diaphragm, positive electrode sheet, and positive electrode shell in order from the negative electrode shell. After assembly, align and press the positive and negative electrode shells, and then use a sealing machine to pressurize and seal. After assembly, let it stand for 4 hours to ensure that the electrolyte fully infiltrates the electrode and diaphragm.

[0075] High voltage activation: The sodium ion button half-cell is then charged at a constant current and constant voltage of 0.1C to 3.75V. After standing, it is discharged at a constant current to 2V. The sodium chromite positive electrode material coated with an inert layer can be obtained by splitting.

[0076] In this example, the sodium ion button half-cell activated by high voltage can be directly subjected to charge and discharge cycle testing without being disassembled, specifically within the range of 2 to 3.6V at 0.5C.

[0077] The measured specific capacity in the first cycle at 2-3.6V is 114.25mAh / g, and the capacity retention rate is 89.17% after 200 cycles at a current of 0.5C, indicating that the positive electrode material of the present invention can make the battery have excellent cycle stability performance. It can further be shown that an inert layer is generated in situ on the surface of the positive electrode material particles of the present invention, which stabilizes the bulk structure and reduces the occurrence of side reactions.

[0078] Example 2: Sodium chromite positive electrode, button half-cell, 3.65V in-situ construction, 3 cycles

[0079] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0080] This embodiment is basically the same as the embodiment 1, except that the charging voltage in the high voltage activation is 3.65V, and the high voltage charge and discharge cycle is repeated 3 times.

[0081] Example 3: Sodium chromite positive electrode, button half-cell, 3.7V in-situ construction, 3 cycles

[0082] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0083] This embodiment is basically the same as the embodiment 1, except that the charging voltage in the high voltage activation is 3.7V, and the high voltage charge and discharge cycle is repeated 3 times.

[0084] Example 4: Sodium chromite positive electrode, button half-cell, 3.75V in-situ construction, 3 cycles

[0085] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0086] This embodiment is substantially the same as the embodiment 1, except that the high voltage charge and discharge cycle is repeated three times during the high voltage activation.

[0087] Example 5: Sodium chromite positive electrode, button half-cell, 3.75V in-situ construction, 5 cycles

[0088] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0089] This embodiment is basically the same as embodiment 1, except that: the high voltage charge and discharge cycle is repeated 5 times during high voltage activation.

[0090] Example 6: Sodium chromite cathode, soft-pack full cell, in-situ construction

[0091] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0092] Specifically:

[0093] Preparation of positive electrode: 9 g of O3-NaCrO2 material, 0.5 g of acetylene black (SP), and 10 g of 5% polyvinylidene fluoride (PVDF) glue (the solvent is N-methylpyrrolidone (NMP), 0.5 g of PVDF), mixed evenly, and then evenly coated on aluminum foil, baked in a vacuum oven at 120°C for 12 hours, and then punched into a positive electrode;

[0094] Preparation of soft-pack full battery: determine the NP ratio to be 1.1, match NaCrO2 as the positive electrode and hard carbon as the negative electrode; stacking, aluminum-plastic film packaging, electrolyte injection, static moistening, and sealing.

[0095] High voltage activation: The soft-pack full battery is then charged at a constant current and constant voltage of 0.1C to 3.6V. After standing, it is discharged at a constant current to 1.5V. The sodium chromite positive electrode material coated with an inert layer can be obtained by splitting.

[0096] In this example, the soft-pack full battery after high-voltage activation can be directly subjected to charge and discharge cycles within the range of 1.5 to 3.5 V (considering hard carbon) at 0.5C without being disassembled.

[0097] The battery capacity retention rate was measured to be 90% after 1500 cycles at 0.5C. Figure 6It can be seen from the STEM data that an inert layer of about 4 nm rock salt phase is in situ generated on the surface of the positive electrode material particles in this example, which can stabilize the bulk structure and reduce side reactions.

[0098] Example 7: Nickel iron sodium manganese oxide cathode, button half cell, 4.15V in situ construction

[0099] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0100] Specifically:

[0101] Preparation of positive electrode: 3.6 g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (purchased from Hefei Kejing Material Technology Co., Ltd., brand) was mixed evenly with 0.2 g of acetylene black (SP) and 4 g of 5% polyvinylidene fluoride (PVDF) glue, and 0.2 g of organic solvent N-methylpyrrolidone (NMP) was added. After mixing evenly, the mixture was evenly coated on aluminum foil, and then placed in a vacuum oven at 120°C and baked for 12 hours before being punched into a positive electrode;

[0102] Preparation of sodium ion button half-cell: Assemble the above-made positive electrode into a sodium ion button half-cell; put the spring, gasket, sodium sheet (negative electrode), diaphragm, positive electrode sheet, and positive electrode shell in order from the negative electrode shell. After assembly, align and press the positive and negative electrode shells, and then use a sealing machine to pressurize and seal. After assembly, let it stand for 4 hours to ensure that the electrolyte fully infiltrates the electrode and diaphragm.

[0103] High voltage activation: The sodium ion button half-cell is then charged at a constant current and constant voltage of 0.1C to 4.15V. After standing, it is discharged at a constant current to 2V. The inert layer-coated sodium nickel iron manganese oxide positive electrode material can be obtained by splitting.

[0104] In this example, the sodium ion button half-cell after high voltage activation can be directly charged and discharged in the range of 2 to 4 V at 0.5C without being disassembled.

[0105] The measured specific capacity in the first cycle at 2-4V is 122.81mAh / g, and the capacity retention rate is 88.58% after 100 cycles at 0.5C current.

[0106] Comparative Example 1: Sodium chromite positive electrode, button half-cell, no high voltage activation treatment

[0107] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0108] The same as Example 1, except that: no high voltage activation treatment is performed, constant current and constant voltage charging is performed at 0.1C to 3.6V, and after standing, constant current discharge is performed to 2V;

[0109] Then the charge and discharge cycles were performed in the range of 2 to 3.6 V at 0.5C.

[0110] Comparative Example 2: Sodium chromite positive electrode, button half-cell, 3.8V in-situ construction

[0111] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0112] The same as Example 1, except that the charging voltage in high voltage activation is 3.8V.

[0113] Practice has shown that 3.8V exceeds the upper limit of the battery's high voltage activation, the material undergoes unexpected changes and the battery performance drops sharply.

[0114] Comparative Example 3: Sodium chromite positive electrode, soft pack full battery, no high voltage activation treatment

[0115] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0116] The same as Example 6, except that: no high voltage activation treatment is performed, constant current and constant voltage charging is performed at 0.1C to 3.5V, and after standing, constant current discharge is performed to 1.5V;

[0117] Then, charge and discharge cycles were performed at 0.5C in the range of 1.5 to 3.5V (considering hard carbon).

[0118] Depend on Figure 7 It can be seen from the STEM data that compared with Example 6, some active substances in Comparative Example 3 are dissolved on the surface, and no rock salt phase inert layer is generated, so the cycle stability is poor.

[0119] Comparative Example 4: Nickel iron sodium manganese oxide positive electrode, button half-cell, no high voltage activation treatment

[0120] This example provides a method for preparing a battery positive electrode material and the battery positive electrode material prepared therefrom, as well as a positive electrode comprising the battery positive electrode material and a battery comprising the positive electrode.

[0121] The same as Example 7, except that: no high voltage activation treatment is performed, constant current and constant voltage charging is performed at 0.1C to 4V, and after standing, constant current discharge is performed to 2V;

[0122] Then the charge and discharge cycles were performed in the range of 2 to 4 V at 0.5C.

[0123] Experiments show that compared with Example 7, Comparative Example 4 did not undergo high voltage treatment and had poor cycle stability.

[0124] Performance Test:

[0125] (1) The cycle performance test data of Examples 1-7 and Comparative Examples 1-4 are shown in Table 1.

[0126] Table 1

[0127]

[0128] (2) See Figure 1 As shown in FIG. 1 , it is a high voltage first cycle activation range diagram of O3-NaCrO2. It can be seen that the voltage platform of O3-NaCrO2 is 3.8V; the charging voltage for voltage activation should be before the irreversible voltage platform of the transition metal layered oxide material (before the 3.8V platform, because after charging to the 3.8V platform, the reversible capacity of the material drops sharply), and higher than the cut-off voltage of the positive electrode material (3.6V);

[0129] Figure 2 The voltage-specific capacity curve of the first cycle of 2-3.6V at 0.5C for Example 1 and Comparative Example 1 (the voltage-specific capacity curve of the activation cycle of 3.75V is shown in FIG. Figure 1 ). The first cycle voltage-specific capacity curve of Example 1 after one cycle of 3.75V high voltage activation. Due to the 3.75V activation, an inert layer is formed in situ on the surface, causing a slight attenuation of capacity;

[0130] Figure 3 The graph of the cycle test of Example 1 and Comparative Example 1 at 0.5C is shown; after Example 1 was activated by a high voltage of 3.75V for one cycle, it was cycled in the range of 2-3.6V, and the 200 cycle stability was 89.17%. Comparative Example 1 was not activated by a high voltage, and the 200 cycle stability was 84.34%, which was significantly lower than that of Example 1;

[0131] Figure 4 The cycle test curves of Example 2, Example 3 and Comparative Example 2 at 0.5C (the voltage-specific capacity curve of the activation circle is shown in Figure 1 ). Example 2 is charged to 3.65V and activated for one cycle, and then tested for cycling within the range of 2-3.6V. The cycle is relatively stable. Example 3 is charged to 3.7V and activated for one cycle, and then tested for cycling within the range of 2-3.6V. The cycle is relatively stable. Comparative Example 2 is charged to 3.8V and activated for one cycle, and then tested for cycling within the range of 2-3.6V. Due to charging to the irreversible voltage platform, the capacity of the material decays, so it is necessary to control the upper limit of high voltage activation to be lower than the irreversible voltage platform;

[0132] Figure 5The following are the cycle test curves of Example 1, Example 4, and Example 5 at 0.5C. The cycle performance of the material was tested at 3.75V high voltage activation for 1, 3, and 5 cycles. After the material was activated for 5 cycles, the cycle stability was the best. However, since the surface will undergo a phase change to an inert layer after each activation cycle, the thickness of the inert layer produced by the material will increase after 5 cycles of high voltage cycling, so the discharge specific capacity of the material will decrease slightly. According to the data in Table 1, although a part of the specific capacity will be lost when the inert layer is too thick, the cycle stability will be significantly improved.

[0133] Figure 6 The STEM image of NaCrO2 activated by high voltage in Example 6 is shown in FIG. Figure 6 It can be seen that a 4nm thick rock salt phase inert layer is produced on the surface of the material;

[0134] Figure 7 This is a STEM image of NaCrO2 in comparative example 3 without high voltage activation. STEM provides high-resolution atomic-level images, which are suitable for element comparison and structural analysis. The heavy element area in the figure is shown as a bright spot, and the white dotted area is the Cr-O layered structure of the layered oxide NaCrO2. The bright spot is the Cr atom, which is composed of Figure 7 It can be seen that there is no rock salt phase inert layer on the surface of the material;

[0135] Figure 8 The first cycle voltage-specific capacity curve under high voltage activation of Example 6 and the first cycle voltage-specific capacity curve without high voltage activation of Comparative Example 3. Example 6 is a NaCrO2 / / HC soft pack battery, the positive electrode material is NaCrO2 coated with an inert layer, and the high voltage activation method is to charge above the cut-off voltage and below the irreversible voltage platform (3.6V vs HC), and construct the inert layer in situ;

[0136] Fig. 9 The graph of the cycle test of Example 6 and Comparative Example 3 at 0.5C. Due to the presence of the rock salt phase inert layer, Example 6 has better cycle stability, and the specific capacity retention rate after 1500 cycles is 92.1%, which is significantly higher than 83.4% of Comparative Example 3;

[0137] Fig.10 The first cycle voltage-specific capacity curve under high voltage activation of Example 7 and the first cycle voltage-specific capacity curve without high voltage activation of Comparative Example 4. The positive electrode material of Example 7 is NaNi coated with an inert layer. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, high voltage activation mode is to charge above the cut-off voltage and below the irreversible voltage platform (4.15V), and construct an inert layer in situ;

[0138] Fig.11The graph is a cycle test curve of Example 7 and Comparative Example 4 at 0.5C. Due to the presence of the rock salt phase inert layer, Example 7 has better cycle stability, and the specific capacity retention rate after 100 cycles is 88.6%, which is significantly higher than 81.9% of Comparative Example 3.

[0139] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0140] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A battery positive electrode material, characterized in that: The battery positive electrode material comprises a bulk layer and an inert layer coated on the bulk layer, wherein the bulk layer comprises a transition metal layered oxide material, and the inert layer comprises a transition metal oxide generated by an irreversible phase change of the transition metal layered oxide material.

2. The battery positive electrode material according to claim 1, characterized in that The transition metal layered oxide material that generates the transition metal oxide in the inert layer comes from the surface portion of the transition metal layered oxide material in the bulk layer.

3. The battery positive electrode material according to claim 1, characterized in that: The thickness of the inert layer is 1-10 nm, further 2-6 nm; and / or the inert layer is a rock salt phase inert layer.

4. The battery positive electrode material according to claim 1, characterized in that The transition metal layered oxide material in the bulk layer and the transition metal layered oxide material in the inert layer are respectively unmodified, or coated and / or doped modified materials.

5. The battery positive electrode material according to claim 1, characterized in that: The chemical composition of the transition metal layered oxide material is Na x MO2, M is selected from transition metals.

6. The battery positive electrode material according to claim 5, characterized in that: M is selected from one or more combinations of Ti, V, Cr, Mn, Fe, Co, and Ni.

7. The battery positive electrode material according to claim 5, characterized in that: In the inert layer, the content ratio of Na to M is 0.2-0.4:1; in the bulk layer, the content ratio of Na to M is 0.5-1:

1.

8. The battery positive electrode material according to claim 1, characterized in that The irreversible phase change includes causing the transition metal layered oxide material to undergo an electrochemical transformation under a voltage.

9. A method for preparing a positive electrode material for a battery according to any one of claims 1 to 8, characterized in that: The preparation method comprises: voltage-activating a battery comprising a positive electrode comprising a transition metal layered oxide material; After the voltage is activated, the battery positive electrode material is generated; The voltage activation comprises: charging the battery to an activation voltage and discharging the battery after standing still; the activation voltage is greater than the cutoff voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change.

10. The method for preparing a positive electrode material for a battery according to claim 9, characterized in that: The preparation process of the positive electrode includes: uniformly mixing the transition metal layered oxide material, the conductive agent, the binder and the solvent, coating the mixture on a current collector and drying the mixture to prepare the positive electrode.

11. The method for preparing a positive electrode material for a battery according to claim 9, characterized in that: The number of times of voltage activation is 1-15 times, further 1-8 times; and / or, during the voltage activation process, the charging is performed at a constant current and constant voltage at 0.01-1C, and the discharging is a constant current discharge.

12. The method for preparing a positive electrode material for a battery according to claim 9, characterized in that: When the transition metal layered oxide material is O3-NaCrO2 material, the activation voltage is 3.65-3.77V; when the transition metal layered oxide material is O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 material, the activation voltage is 4.15-4.27V; and / or, the battery positive electrode material is obtained by disassembling the battery after the voltage activation; and / or, under the voltage activation, the transition metal layered oxide material undergoes a phase change from the surface, and an inert layer on the surface is generated in situ to generate the battery positive electrode material with a coating structure.

13. A battery positive electrode material, characterized in that: The battery positive electrode material is generated by causing a transition metal layered oxide material to undergo electrochemical transformation at an activation voltage, wherein the activation voltage is greater than a cutoff voltage of the transition metal layered oxide material and less than a voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change.

14. A positive electrode sheet for a battery, characterized in that: The battery positive electrode sheet comprises the battery positive electrode material according to any one of claims 1-8 and 13.

15. A method for preparing a positive electrode sheet of a battery, characterized in that: The preparation method comprises: (1) assembling a positive electrode comprising a transition metal layered oxide material into a battery; (2) voltage activation of the battery; wherein the voltage activation comprises: charging the battery to an activation voltage, and discharging the battery after standing; the activation voltage is greater than the cutoff voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change; (3) Disassemble the battery processed in step (2) to obtain the battery positive electrode sheet.

16. A battery, characterized in that: The battery comprises the battery positive electrode sheet according to claim 14 or the battery positive electrode sheet prepared by the method for preparing the battery positive electrode sheet according to claim 15; further, the battery comprises a sodium ion battery or a lithium ion battery.

17. A method for preparing a battery, the method comprising a battery formation process, characterized in that: The formation process comprises: The battery is voltage activated, wherein the voltage activation comprises: charging the battery to an activation voltage, and discharging the battery after standing; the activation voltage is greater than the cut-off voltage of the transition metal layered oxide material and less than the voltage platform at which the transition metal layered oxide material undergoes an irreversible phase change; The battery includes a positive electrode comprising a transition metal layered oxide material.

Citation Information

Patent Citations

  • In-situ surface modification method of lithium-rich manganese-based layered positive electrode material

    CN115784313A

  • Sodium-ion battery positive electrode material, preparation method thereof and positive plate

    CN118448615A

  • Post-treatment method of lithium secondary battery

    US20200328400A1

  • Layered sodium-ion battery positive electrode material, preparation method therefor, and use thereof

    WO2024093126A1

Cited By

  • Core-shell structure sodium ion battery positive electrode material and in-situ coating preparation method thereof

    CN121366885A

  • A core-shell structure sodium ion battery positive electrode material and an in-situ coating preparation method thereof

    CN121366885B